2004
DOI: 10.1262/jrd.50.87
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Function of Whey Acidic Protein in the Cell-Cycle Progression of Mouse Mammary Epithelial Cells (EpH4/K6 Cells)

Abstract: Abstract. Although the biological role for whey acidic protein (WAP) in milk has been suggested, its true function is not known. This paper describes evidence for WAP function in the cell-cycle progression of EpH4/K6 (EpH4), mammary epithelial cells in vitro. The forced expression of exogenous WAP significantly impaired the proliferation of EpH4 cells, whereas it did not affect that of . Recently, it has also isolated from the milk of pigs [5,6], and three marsupial species, tamer wallaby [7], red kangaroo [8]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
11
1
Order By: Relevance
“…This observation was recently confirmed by H. Tojo and his group (Ikeda et al, 2002). Futhermore, they demonstrated that mouse WAP plays an inhibitory role in the cell cycle progression of the mouse mammary epithelial cell lines EpH4/K6 and HC11 (Ikeda et al, 2004;Nukumi et al, 2004) and in mouse (MMT) and human (MCF-7) mammary tumor cells (Nukumi et al, 2005), most likely by decreasing the expression of cyclinD1 known to be essential for the development of the mammary gland (Sicinski et al, 1995). Despite the fact that they did not demonstrate a decrease in the expression of the cyclin D1 gene in the mammary gland of mice overexpressing WAP, their results should be taken into consideration.…”
Section: Potential Roles For Wapmentioning
confidence: 59%
“…This observation was recently confirmed by H. Tojo and his group (Ikeda et al, 2002). Futhermore, they demonstrated that mouse WAP plays an inhibitory role in the cell cycle progression of the mouse mammary epithelial cell lines EpH4/K6 and HC11 (Ikeda et al, 2004;Nukumi et al, 2004) and in mouse (MMT) and human (MCF-7) mammary tumor cells (Nukumi et al, 2005), most likely by decreasing the expression of cyclinD1 known to be essential for the development of the mammary gland (Sicinski et al, 1995). Despite the fact that they did not demonstrate a decrease in the expression of the cyclin D1 gene in the mammary gland of mice overexpressing WAP, their results should be taken into consideration.…”
Section: Potential Roles For Wapmentioning
confidence: 59%
“…Robinson et al [22] have indicated that precocious expression of WAP results in terminal differentiation of alveolar cells during mid-pregnancy, which in turn prevents the alveolar structures from proliferating. We previously reported that the enforced expression of WAP transgene significantly impaired proliferation of two mammary epithelial cell lines, EpH4/K6 and HC11 cells, and decreased the expression of cyclin D1 through cell-cycle progression from the G1 to S phase [23,24].…”
mentioning
confidence: 99%
“…However, only a few studies have attempted to determine the actual function of WAP [3,20]. We have previously reported that WAP inhibits the proliferation of mouse mammary epithelial cells in vivo and in vitro [12,[14][15][16][17] and has a function in reducing tumorigenesis and invasion of mammary cancer cells [18]. A number of antibacterial proteins with a WAP motif have been identified in a variety of tissues,-e.g., elafin [22], eppin [24], SLPI [25], SWAM1 and SWAM2 [10], although the molecular antibacterial mechanism of these proteins is not entirely clear.…”
mentioning
confidence: 99%